2017
DOI: 10.1007/s00345-016-1997-x
|View full text |Cite
|
Sign up to set email alerts
|

Critical appraisal of consecutive 36 cases of post renal transplant lymphocele: a proposed algorithm

Abstract: Significant number of lymphocele post renal transplant may be asymptomatic but still cause deterioration of renal function even without causing obstructive uropathy. Lymphoceles causing renal deterioration or symptoms should be managed in a step ladder fashion starting from percutaneous drainage to laparoscopic marsupilization to open surgical approach. Asymptomatic recurrences post marsupialization are common and should be only closely observed unless they become symptomatic or cause deterioration of renal fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…). Eighty‐seven articles met the inclusion criteria and were included in the report. Seventy‐six articles reported on lymphoceles only, four articles on lymphorrhoea, and seven articles on lymphocele and lymphorrhoea.…”
Section: Resultsmentioning
confidence: 99%
“…). Eighty‐seven articles met the inclusion criteria and were included in the report. Seventy‐six articles reported on lymphoceles only, four articles on lymphorrhoea, and seven articles on lymphocele and lymphorrhoea.…”
Section: Resultsmentioning
confidence: 99%
“…Another more radical option is marsupialization. This surgical procedure offers low morbidity, fast recovery, and a low recurrence rate (<15%) 13,14 …”
Section: Discussionmentioning
confidence: 99%
“…This surgical procedure offers low morbidity, fast recovery, and a low recurrence rate (<15%). 13,14 Lymphatic embolization has been an emerging technique for several years to treat PL. Baek et al reported a 95% efficacy in a series of 21 patients after gynecological surgery.…”
Section: Discussionmentioning
confidence: 99%
“…6 Similarly, Choudhrie et al, and Singh et al, from India, had successfully cured 80% (4 out of 5) and 85.7 % (18 out of 21) lymphocele patients by laparoscopic marsupialization in their respective series. 7,8 IKDRC, Ahmedabad, is the leading renal transplant center in West India, where laparoscopic urological surgeries are performed on daily basis.…”
Section: Introductionmentioning
confidence: 99%